Impacts of organizational support on rice farmers’ adoption of green production technologies—implications for food security and environmental sustainability - Zhang, Xu; Zhang, Yuhan; Liu, Yang; Ye, Feng; Liao, Wenmei (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe relentless focus on maximizing production has exacerbated ecological challenges, including agricultural surface pollution, soil crusting, and farmland degradation, which increasingly threaten sustainable development. Agricultural green production technologies are essential for balancing food security with environmental sustainability.MethodsThis study examines the role of organizational support in fostering farmers’ adoption of agricultural green production technologies, using survey data from 1,426 rice farmers in Jiangxi Province, China. Ordered logit and moderated mediation models reveal a robust positive effect of organizational support on agricultural green production technology adoption, even after addressing endogeneity concerns.Results and discussionThe findings highlight that the effect of organizational support is more pronounced among farmers with agricultural insurance and those primarily engaged in farming. Mechanistic analysis shows that operation scale partially mediates the relationship between organizational support and agricultural green production technology adoption, accounting for 7.76% of the total effect. Furthermore, social capital acts as a positive moderator, amplifying the impact of organizational support on the operation scale and, subsequently, on agricultural green production technology adoption. These results underscore the need to enhance organizational support measures, promote moderate-scale farming, and cultivate social capital as critical strategies for advancing green agricultural practices.